The Impact of Traditional Homestead Vegetable Cultivation on the Improvement of Livelihood of Rural Women in Bangladesh - Akter , Aysha; Ahmad, Nobaya; Bagum, Thahamina; Islam, Md Monirul; Rahma, Mohammad Mizanur; Hossain , Mohammad Imtiaz (Asian Journal of Agriculture and Rural Development, 2019)
The aim of the study was to determine the level of acceptability of traditional homestead vegetable cultivation practices by rural women in the northeastern parts of Bangladesh and its impact on their livelihood. A structured interview schedule was applied to collect data. Data were collected from 100 women from two villages of South Surma Upazila in the Sylhet district and correlation tests were conducted to examine the relationship between the relevant dependent and independent variables. The results showed that 68% of rural women had a moderately favourable opinion of vegetable cultivation regarding changes in the livelihood of rural women, while 20% had low opinion and 12% had high opinion of traditional homestead vegetable practices. The majority (59%) of the women had moderately adopted traditional homestead vegetable cultivation practices compared to 24% who had adopted them little and 17% who had adopted them highly. Computed (r) values indicate that education, homestead area, family income, knowledge of homestead vegetable cultivation, availability of credit, and exposure of the rural women to communication had a significantly positive relationship to their attitudes to changes in livelihood.